Hambatan Pelaksanaan Restorative Justice Pada Tindak Pidana Narkotika Di Kepolisian Resort Gorontalo Kota - Mohammad Hakim Pratama Rahim; Dian Ekawaty Ismail; Apripari Apripari (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to determine the implementation of restorative justice in narcotics crimes at the Gorontalo City Resort Police, based on the title raised in this research. This research uses empirical legal research, because this research is based on the reciprocal relationship between law and other institutions. It is said to be empirical because it is based on real data or facts. This research aims to look for primary data or what can also be called field data on the implementation of restorative justice in drug crimes. The results of this research show that the implementation of restorative justice in drug crimes is not solely for all drug users, but there are several provisions in accordance with Perpol number 8 of 2001. The provisions so that restorative justice can be carried out include: the person is not involved in a drug network, drugs that are there is only personal use, not resale, not a resinipis, namely a second arrest, and the evidence does not exceed the amount and so on. So apart from these provisions, RJ cannot be carried out. In accordance with prosecutor's guidelines number 18 of 2021 concerning the resolution of handling criminal cases for victims of narcotics abuse, it is carried out through rehabilitation with a restorative justice approach. Apart from that, the obstacles in implementing restorative justice, according to information, are several factors, namely internally, namely obstacles in the BNN reporting or assessment process due to inappropriate time, namely exceeding the 3x24 hour time frame, and external factors, namely the lack of cooperation with the community, which causes delays in reporting. and when the arrest was made, the perpetrators did not admit that the items belonged to them, so 2 witnesses were needed in the form of the local RT head so that the process could continue.